Violin Sonatas [de Wolfgang Amadeus Mozart] : Violin and Keyboard = Violin Sonatas [de Wolfgang Amadeus Mozart] : Violine und Klavier = Violin Sonatas [de Wolfgang Amadeus Mozart] : violon et clavier = Violin Sonatas [de Wolfgang Amadeus Mozart] : violino e pianoforte o clavicembalo - Mozart, Wolfgang Amadeus ((Complete Mozart Edition ;)
Contiene: Sonatas para violín KV 547, KV 404/385d, KV 402/385e, KV 403/385c, KV 396/385f, KV 372, KV 359/374a, KV 46d, KV 46e, KV 5, KV 7, KV 8, KV 9, KV 10, KV 11, KV12, KV 13, KV 14, KV 15, KV 26, KV 27, KV 28, KV 29, KV 30, KV 31, KV 296, KV 301/293a, KV 302/293b, KV 303/293c, KV 304/300c, KV 305/293d, KV 306/3001, KV 360/374b, KV 376/374d, KV 377/374e, KV 378/317d, KV 379/373a, KV 380/374f, KV 454, KV 481, KV 526.